2019
DOI: 10.1002/jmor.20954
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical similarity across ontogeny of digging muscles in an Australian marsupial (Isoodon fusciventer)

Abstract: Many mammals dig, either during foraging to access subsurface food resources, or in creating burrows for shelter. Digging requires large forces produced by muscles and transmitted to the soil via the skeletal system; thus fossorial mammals tend to have characteristic modifications of the musculoskeletal system that reflect their digging ability. Bandicoots (Marsupialia: Peramelidae) scratch‐dig mainly to source food, searching for subterranean food items including invertebrates, seeds, and fungi. They have mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…The species displays adaptations of both muscle and bone anatomy associated with scratch‐digging (Warburton et al, ). This study builds on previous findings that showed Quenda force generation capacity (PCSA) showed differential growth between main movers of the recovery stroke and the power stroke of scratch‐digging (Martin, Warburton, Travouillon, & Fleming, ). We therefore predicted that muscles associated with the power‐stroke of digging will have disproportionate influence on shape change of the long bones.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The species displays adaptations of both muscle and bone anatomy associated with scratch‐digging (Warburton et al, ). This study builds on previous findings that showed Quenda force generation capacity (PCSA) showed differential growth between main movers of the recovery stroke and the power stroke of scratch‐digging (Martin, Warburton, Travouillon, & Fleming, ). We therefore predicted that muscles associated with the power‐stroke of digging will have disproportionate influence on shape change of the long bones.…”
Section: Introductionsupporting
confidence: 71%
“…Quenda are sexually dimorphic in body mass (Warburton & Travouillon, ) and we therefore predicted that there may be some sex differences in forelimb musculature or bone shape. Despite these differences, we previously identified that Quenda forelimb muscle anatomy (muscle mass, PCSA, and fiber length) showed no significant difference between the sexes (Martin et al, ). Furthermore, there were only minor sex differences in a single forelimb bone in the Quenda in the present study; the third metacarpal showed shape differences between the sexes, with males having a smaller, less elongated proximal end.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…; Martin et al. ). Unfortunately, no data is presently available for ontogenetic variation or scaling in muscle architecture for perissodactyls, and therefore scaling of juvenile Tapirus data to an adult size was not performed.…”
Section: Methodsmentioning
confidence: 97%
“…As equids are much larger than juvenile tapirs, direct comparison of muscle mass was considered unsuitable. Ontogenetic studies of mammalian and avian muscle and tendon anatomy suggest that limb muscles can scale both allometrically and isometrically through ontogeny, dependent upon the muscle and the taxon (Miller et al 2008;Olson et al 2018;Martin et al 2019). Unfortunately, no data is presently available for ontogenetic variation or scaling in muscle architecture for perissodactyls, and therefore scaling of juvenile Tapirus data to an adult size was not performed.…”
Section: Statistical Comparisonsmentioning
confidence: 99%